ACUTE 2,4-DICHLOROPHENOXYACETIC ACID INTOXICATION IN CATTLE - Paulino, C. A.; Oliveira, G. H.; Palermoneto, J. (Comparative Toxicology Lab Kansas State Univ, 1994)
The acute toxicity of 2,4-dichlorophenoxyacetic acid (2,4-D) was studied in cattle. Steers were orally treated with 100, 300 or 600 mg 2,4-D/kg. Behavioral alterations, heart and respiratory functions, rectal temperature and ruminal movements were observed at 2, 4, 8, 12, 24, 48, 72 and 96 h after treatments. At these moments, blood and urine samples were collected and serum 2,4-D levels were determined. Results show that animals' vital functions and hematocrit were not modified by the herbicide. Other signs were dose and time-dependent and included motor alterations (weakness, lethargy, decreased general activity) and decreased ruminal movements and proteinuria. The herbicide was rapidly excreted and the intoxication signs were completely reversed. 2,4-D is an herbicide of small toxicological consequences for cattle kept under in natural grazing systems.